Who benefits from a dietary online intervention? Evidence from Italy, Spain and Greece. Issue 5 (10th November 2016) - Schwarzer, Ralf; Fleig, Lena; Warner, Lisa M; Gholami, Maryam; Serra-Majem, Lluis; Ngo, Joy; Roman-Viñas, Blanca; Ribas-Barba, Lourdes; Distante, Alessandro; Ntzani, Evangelia; Giannakis, George; Brandi, Maria L
Abstract: Objective: The traditional Mediterranean diet includes high consumption of fruits, vegetables, olive oil, legumes, cereals and nuts, moderate to high intake of fish and dairy products, and low consumption of meat products. Intervention effects to improve adoption of this diet may vary in terms of individuals' motivational or volitional prerequisites. In the context of a three-country research collaboration, intervention effects on these psychological constructs for increasing adoption of the Mediterranean diet were examined. Design: An intervention was conducted to improve Mediterranean diet consumption with a two-month follow-up. Linear multiple-level models examined which psychological constructs (outcome expectancies, planning, action control and stage of change) were associated with changes in diet scores. Setting: Web-based intervention in Italy, Spain and Greece. Subjects: Adults ( n 454; mean age 42·2 (sd 10·4) years, range 18–65 years; n 112 at follow-up). Results: Analyses yielded an overall increase in the Mediterranean diet scores. Moreover, there were interactions between time and all four psychological constructs on these changes. Participants with lower levels of baseline outcome expectancies, planning, action control and stage of change were found to show steeper slopes, thus greater behavioural adoption, than those who started out with higher levels. Conclusions: The intervention produced overall improvements in Mediterranean diet consumption, with outcome expectancies, planning, action control and stage of change operating as moderators, indicating that those with lower motivational or volitional prerequisites gained more from the online intervention. Individual differences in participants' readiness for change need to be taken into account to gauge who would benefit most from the given treatment.